How do you simplify -5sqrt18?

2 Answers
Jun 23, 2018

-15sqrt(2)

Explanation:

-5sqrt(18)

(Then, since sqrt(ab)=sqrt(a)*sqrt(b))

=-5sqrt(9)sqrt(2)
=-5*3*sqrt(2)
=-15sqrt(2)

Jun 23, 2018

See a solution process below:

Explanation:

Use this rule for radicals to simplify the expression:

sqrt(color(red)(a) * color(blue)(b)) = sqrt(color(red)(a)) * sqrt(color(blue)(b))

-5sqrt(18) => -5sqrt(color(red)(9) * color(blue)(2)) => -5sqrt(color(red)(9)) * sqrt(color(blue)(2)) => -5 * 3sqrt(2) => -15sqrt(2)